Combining local and remote laboratories for the interactive learning of industrial automation - Cordeiro, Armando (2018)
This study presents an educational project for the interactive learning of Industrial Automation. The objective of this project is to allow Bachelor's and Master's students of Electrical Engineering of the Instituto Superior de Engenharia de Lisboa (ISEL-IPL) to learn theoretical and practical fundamentals of Industrial Automation through local and remote laboratory experiments. The proposed pedagogical activities, together with the flexibility of the solution adopted for the laboratory experiments, allow students to acquire advanced knowledge regarding Programmable Logic Controller (PLC) programming languages, Supervisory Control and Data Acquisition (SCADA) applications and industrial communication networks, among other aspects. The main benefits of this educational project are the motivation to engage in problem solving, developing mental strategies based on new hypotheses, step-by-step knowledge construction, and the possibility to interact and change, locally or remotely, the developed programs. Additionally, the adopted laboratory architecture is based on industrial hardware and software, like those found in real applications.